Organizational Politics and Job Satisfaction: Mediation and Moderation of Political Skills - Abdullah W. Jabid; Irfandi Buamonabot; Johan Fahri; Muhammad Asril Arilaha (Bina Nusantara University, 2021)
Politics in organizations has been a concern for the job satisfaction of the employees. The minimum researchon how politics are in an organization plays an essential role in job satisfaction. In this context, organizationalpolitics are suspected of contributing to employees’ job satisfaction. However, there is limited research discussingpolitical skill as a ‘bridge’ variable between organizational politics and job satisfaction. The research examinedthe impact of moderation and mediation of political skill on organizational politics and job satisfaction in TernateCity government. It applied a quantitative method. The population was 240 employees from the middle to topmanagement in local government offices. With purposive sampling, 86 respondents working in the RegionalGovernment Work Unit of Ternate City were involved in the survey. The research used a hierarchical regressionanalysis as a statistical analysis and IBM SPSS statistics Version 24. The results show several results. First,organizational politics influences job satisfaction negatively. Second, organizational politics affect political skillpositively. Third, political skill strengthens the relationship between organizational politics and job satisfaction. Itmediates and moderates the full relationship between organizational politics and job satisfaction.